2018
DOI: 10.21608/asejaiqjsae.2018.5820
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Land and Water Productivity by Intercropping Sunflower with Peanut under Sprinkler Irrigation

Abstract: Effective intercropping pattern, use of highly efficient irrigation system and proper irrigation scheduling are one of the current challenges in agriculture sector for saving water, maximizing crop production and economic benefits. Thus, a two-year field experiment was conducted at Ismailia Research Station (30o 35' N latitude, 30o 26' E longitude, 20.0m above MSL), Egypt during the two growing seasons of 2016 and 2017 to study the effect of three irrigation treatments (1.2, 1.0 and 0.8 ETo calculated by the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…These data reveal that intercropping patterns responded similarly to irrigation water levels for all the studied peanut traits. These results are in agreement with those obtained by El-Mehy et al [15] who reported that the interaction between irrigation treatments and intercropping patterns had no significant effect on pod yield ha −1 in both seasons.…”
Section: The Interaction Between Irrigation Water Levels and Intercrosupporting
confidence: 93%
See 2 more Smart Citations
“…These data reveal that intercropping patterns responded similarly to irrigation water levels for all the studied peanut traits. These results are in agreement with those obtained by El-Mehy et al [15] who reported that the interaction between irrigation treatments and intercropping patterns had no significant effect on pod yield ha −1 in both seasons.…”
Section: The Interaction Between Irrigation Water Levels and Intercrosupporting
confidence: 93%
“…These data reveal that each of these two factors act dependently on head diameter and head seed weight. These results are parallel with those obtained by El-Mehy et al [15] who demonstrated that head diameter and head weight were influenced significantly by interaction between irrigation treatments and intercropping patterns in both seasons.…”
Section: ) Sunflower Traitssupporting
confidence: 91%
See 1 more Smart Citation
“…The few previous studies on intercropping sunflower with peanut in Egypt dealt with either the appropriate sunflower planting density (Abd El-Zaher et al, 2009 andEl-Mehy et al, 2018) and/or appropriate irrigation amounts (El-Mehy et al, 2018). Thus, this investigation was done with the aim to determine the suitable arrangement for sunflower and peanut in an intercropping system, the required irrigation water amounts, and the required potassium fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Abd El-Zaher et al (2009) reported that highest value for yield of peanut were obtained with 100% of peanut planting density and 33% of sunflower planting density. A reduced sunflower planting density, namely 25% was found to result in the highest peanut yield in sunflower intercropped with peanut system (El-Mehy et al, 2018).…”
Section: Introductionmentioning
confidence: 90%